Saúde óssea de pacientes com síndrome dos ovários policísticos: revisão sistemática e metanálise - Piovezan, Júlia Mottecy (2018)
Background: Polycystic ovary syndrome (PCOS) has reproductive and metabolic aspects that may affect bone health. Controversial results from different studies led to uncertainty whether PCOS might improve or deteriorate bone health. Objective and rationale: This study aimed to investigate the impact of PCOS on bone markers, bone mineral density (BMD) and fracture risk. Search methods: A systematic review and meta-analysis was carried out. PubMed, EMBASE and Cochrane databases were searched for eligible studies from 1st of January of 1990 to 9th of October of 2018. Eligible studies enrolled women older than 18 years with PCOS, which should be diagnosed by the Rotterdam Consensus, the Androgen Excess Society, the National Institutes of Health Consensus or the International Classification of Diseases. The studies were grouped according to the patients’ mean body mass index (BMI): <27 kg/m2 or ³ 27 kg/m2. The results were polled as mean difference (MD), standardised mean difference (SMD) and hazard ratio (HR). Outcomes: Overall, 921 studies were retrieved, and 31 duplicated studies were removed. After screening the titles and abstracts, 80 studies were eligible for full-text reading. Of those, 23 studies remained for qualitative synthesis. With the exception of one study, all studies were considered high quality based on the Newcastle-Ottawa scale (NOS; score ³6). Meta-analysis was performed in 21 studies, with a total of 31,383 women with PCOS and 102,797 controls. Women with PCOS with BMI<27 kg/m2 had lower BMD of the total femur (MD, -0.04; 95% confidence interval [CI], -0.07 to 0.00; I2=31%; p=0.22) and spine (MD, -0.07; 95% CI, -0.13 to -0.01; I2=70%; p<0.01) when compared with the control group, whereas women with BMI³27 kg/m2 had no difference (femur: MD, 0.02; 95% CI, -0.02 to 0.05; I2=20%, p=0.29; spine: MD, 0.02; 95% CI, -0.06 to 0.05; I2=0%; p=0.84). Osteocalcin was remarkably reduced in women with PCOS with BMI<27 kg/m2 (SMD, -2.68; 95% CI, -4.70 to -0.67; I2=98%; p<0.01), but in women with BMI³27 kg/m2, there were no differences between PCOS and controls. Few studies (n=3) addressed the incidence of bone fractures in women with PCOS. The HR for total bone fractures did not identify differences between women with PCOS and controls. Wider implications: On the basis of the available evidence, it is possible to assume that PCOS is associated with unfavourable impact on bone health. Women with PCOS exhibited reduced BMD in the spine (trabecular bone) and decreased bone formation, as manifested by lower levels of circulating osteocalcin. However, many of these studies included premenopausal women, who have not yet achieved peak bone mass. Hence, further prospective studies are necessary to clarify the existence increased risk of fractures in women with PCOS.